PENGEMBANGAN MEDIA SCRAPBOOK BERBASIS CERITA ASAL USUL PACITAN UNTUK MENINGKATKAN KETERAMPILAN MEMBACA - Shofiyullah anwar; Vit Ardhyantama; Mega Isvandiana Purnamasari (PGSD STKIP PGRI Pacitan, 2026)
This study aims to determine: (1) scrapbook media development procedures; (2) the level of effectiveness of scrapbook media development; (3) the results of scrapbook media development. This type of research is research and development (R&D) with the ADDIE development model. The product was tested on 6 grade I elementary school students in a small group trial. The feasibility of the product is based on the results of the assessment of language experts, media experts, learning experts, and responses of grade I elementary school students as test subjects. Data collection techniques used observation, interviews, questionnaires, tests, and documentation. Data analysis used product validity level and trial data analysis. The results showed (1) scrapbook media had been developed with the ADDIE development model with expert trials and validation; (2) a score ≥75 of 91%; (3) linguist assessment averaged a score of 4.14